Life‐history traits and the fate of translocated populations. Issue 4 (25th January 2019) - Ducatez, Simon; Shine, Rick
Abstract: Attempts to identify predictors and mechanisms of invasion success have been weakened by poor data quality, mostly because monitoring does not begin immediately after introduction events. To overcome this issue, we used data from conservation translocations of threatened bird species. We analyzed information on >1200 translocation events of >150 bird species to investigate how life‐history traits affect population establishment measured based on rates of survival and reproduction. Species position along the slow–fast life‐history continuum was a key predictor of translocation success. Species with fast‐paced life histories were less likely to survive (over both short‐ and mid‐term) and more likely to breed successfully than species with slow life histories. The temporal partitioning of reproductive effort (number of clutches per year) also affected the probability of successful reproduction. Our results illustrate how conservation‐motivated reintroduction programs can provide proxies for the initial stages of the invasion process, enabling empirical tests of predictions from life‐history theory and informing management. Abstract : Article impact statement : After translocations for conservation purposes, bird survival and breeding success depend on their life history. Abstract : Atributos de las Historias de Vida y el Destino de las Poblaciones Reubicadas Resumen: Los intentos por identificar los pronosticadores y los mecanismos del éxito de invasión han sido debilitados por la poca calidad de los datos, principalmente porque el monitoreo no inicia inmediatamente después de los eventos de introducción. Para superar este tema, usamos datos a partir de las reubicaciones por conservación de especies amenazadas de aves. Analizamos la información de más de 1, 200 eventos de reubicación para más de 150 especies de aves y así investigar cómo los atributos de las historias de vida afectan el establecimiento de la población medido con base en tasas de supervivencia y reproducción. La posición de las especies a lo largo del continuo de historias de vida lenta‐rápida fue un pronosticador importante para el éxito de la reubicación. Las especies con historias de vida rápidas tuvieron una menor posibilidad de sobrevivir (tanto a corto como a mediano plazo) y una mayor probabilidad de reproducirse exitosamente que las especies con historias de vida lentas. La división temporal del esfuerzo reproductivo (número de puestas por año) también afectó la probabilidad del éxito de la reproducción. Nuestros resultados ilustran cómo los programas de reintroducción motivados por la conservación pueden proporcionar sustitutos para los estadios iniciales del proceso de invasión, permitiendo pruebas empíricas a partir de la teoría de la historia de vida e informando a los administradores. 摘要: 对物种能否成功引入的预测及其机制的研究面临着低质量数据的不利影响, 这主要是因为在引入物种后没有立即开始监控。为解决这个问题, 我们利用濒危鸟类迁地保护的数据, 分析了超过 150 种鸟类 1200 多次的迁地保护事件, 基于存活率和繁殖率来研究生活史特征如何影响种群的建立。物种在从慢到快的生活史特征连续变化区间中的位置是预测迁地保护能否成功的关键因素。生活史快的物种比生活史慢的物种短期和中期的存活率更低, 但繁殖成功率更高。在繁殖上的时间分配 (每年繁殖窝数) 也会影响繁殖成功率。我们的结果阐释了如何利用以保护为动机的重引入项目模拟入侵过程的最初阶段, 来对生活史理论中的预测因素进行实证检验, 并为管理提供信息。【翻译: 胡怡思; 审校: 聂永刚】